Multicriteria approach to the selection of the training model of dangerous goods transport advisors in the Ministry of Defense and the Serbian Army - Lukovac, Vesko M.; Zeljić Drakulić, Svetlana R.; Tomić, Lazar M.; Liu, Feng (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: Progress of science and development of new technologies brings increased everyday use of goods with potential human safety and health hazards. The aim of this paper was to select a model for training individuals who are to perform the function of dangerous goods transport advisors in the Ministry of Defense (MD) and the Serbian Armed Forces (SAF). Methods: The problem was solved through the use of the AHP (Analytic Hierarchy Process) with ten subject-matter experts involved, who all contributed - within their individual competency level, with different individual weight of knowledge - to the final decision. Results: The stability of the final decision was confirmed with a dynamic sensitivity analysis through the use of Expert Choice 2000 software. Connclusion: The results of the conducted research favored the model by which the training should be conducted relying on one’s own resources.